Impact of resveratrol-loaded liposomal nanocarriers on heat-stressed broiler chickens: Effects on performance, sirtuin expression, oxidative stress regulators, and muscle building factors - Kishawy, Asmaa T. Y.; Ibrahim, Doaa; Roushdy, Elshimaa M.; Moustafa, Amira; Eldemery, Fatma; Hussein, Elham M.; Hassan, Fardos A. M.; Elazab, Sara T.; Elabbasy, Mohamed Tharwat; Kanwal, Raheela; Kamel, Walid M.; Atteya, Mohamed R.; et al. (Frontiers in Veterinary Science, 2023)
Climate change is considered to be the primary cause of heat stress (HS) in broiler chickens. Owing to the unique properties of extracted polyphenols, resveratrol-loaded liposomal nanoparticles (Resv-Lipo NPs) were first explored to mitigate the harmful effects of HS. The dietary role of Resv-Lipo NPs in heat-stressed birds was investigated based on their growth performance, antioxidative potential, and the expression of heat shock proteins, sirtuins, antioxidant, immune, and muscle-building related genes. A total of 250 1-day-old Ross 308 broiler chickens were divided into five experimental groups (5 replicates/group, 10 birds/replicate) for 42 days as follows: the control group was fed a basal diet and reared in thermoneutral conditions, and the other four HS groups were fed a basal diet supplemented with Resv-Lipo NPsI, II, and III at the levels of 0, 50, 100, and 150 mg/kg diet, respectively. The results indicated that supplementation with Resv-Lipo NP improved the growth rate of the HS group. The Resv-Lipo NP group showed the most significant improvement in body weight gain (p < 0.05) and FCR. Additionally, post-HS exposure, the groups that received Resv-Lipo NPs showed restored functions of the kidney and the liver as well as improvements in the lipid profile. The restoration occurred especially at higher levels in the Resv-Lipo NP group compared to the HS group. The elevated corticosterone and T3 and T4 hormone levels in the HS group returned to the normal range in the Resv-Lipo NPsIII group. Additionally, the HS groups supplemented with Resv-Lipo NPs showed an improvement in serum and muscle antioxidant biomarkers. The upregulation of the muscle and intestinal antioxidant-related genes (SOD, CAT, GSH-PX, NR-f2, and HO-1) and the muscle-building genes (myostatin, MyoD, and mTOR) was observed with increasing the level of Resv-Lipo NPs. Heat stress upregulated heat shock proteins (HSP) 70 and 90 gene expression, which was restored to normal levels in HS+Resv-Lipo NPsIII. Moreover, the expression of sirtuin 1, 3, and 7 (SIRT1, SIRT3, and SIRT7) genes was increased (p < 0.05) in the liver of the HS groups that received Resv-Lipo NPs in a dose-dependent manner. Notably, the upregulation of proinflammatory cytokines in the HS group was restored in the HS groups that received Resv-Lipo NPs. Supplementation with Resv-Lipo NPs can mitigate the harmful impact of HS and consequently improve the performance of broiler chickens.